Towards deconstruction of the Sternopygus macrurus species complex (Gymnotiformes: Sternopygidae): description of a new species from the Pacific Coast of Colombia - Torgersen, Kevin T.; Galindo-Cuervo, Aleidy M.; Ortega-Lara, Armando; Lujan, Nathan K.; Reis, Roberto E.; Albert, James S. (Zootaxa, 2026)
A new species of longtail electric knifefish, Sternopygus embera sp. nov., is described from the trans-Andean Río Baudó and Río San Juan basins of the Pacific coast of northwestern Colombia. The new species is diagnosed from all congeners by a unique combination of characters, including the complete lack of a humeral spot, morphology of the Weberian apparatus, lack of pigment bars or saddles, possession of endopterygoid teeth, vertically-oriented ascending endopterygoid process, a short snout, convex dorsal margin of neurocranium in adults, and 22–23 precaudal vertebrae. Despite sharing more external morphological similarities with species of the S. macrurus complex, the new species is phylogenetically nested within the larger-bodied and longer-snouted trans-Andean S. aequilabiatus species group, based on phylogenetic analysis of the mitochondrial barcode gene. Alternative hypotheses for these contrasting results, including mitochondrial introgression, incomplete lineage sorting, and paedomorphosis, are discussed. The description of this species is a step towards deconstructing the S. macrurus complex ahead of a future systematic revision.